Acceptability of minimal invasive tissue sampling (MITS) for stillbirths in Eastern Uganda - Martin Chebet; Kathy Burgoine; Joseph Rujumba; Noela Regina Akwi Okalany; Peter Olupot-Olupot; Thorkild Tylleskar; Andrew D. Weeks; Agnes Napyo; David Mukunya; Ingunn Marie S. Engebretsen (PLoS ONE, 2025)
Background In sub-Saharan Africa, stillbirth rates remain high. To design effective interventions to reduce stillbirths, accurate determination of their aetiology is important. Conventional autopsy for accurate confirmation of cause is not acceptable or feasible in several societies in sub-Saharan Africa; minimal invasive tissue sampling (MITS), is a recently developed, less invasive alternative. In this study, we explored the acceptability of MITS in the community and among healthcare workers in Uganda to guide the future implementation. Methods A qualitative study was done among community members and healthcare workers in Mbale in Eastern Uganda. We undertook in-depth interviews and focus group discussions in English or local languages. Interviews were audio-recorded, transcribed as necessary prior to formal content analysis. The themes were organised using NVivo software and presented according to Sekhon’s theoretical framework. Results Overall, participants preferred the idea of MITS to conventional autopsy because of the perception that it was fast, maintained the facial appearance and kept the body intact. It was thought that the procedure would improve the detection of the cause of stillbirths, which in turn would help to prevent future stillbirths. It would also resolve conflicts in the community between community members or the women and the healthcare workers about the cause of a stillbirth. It was suggested that some community members may not approve of MITS because of their religious beliefs; the fear that the body parts may be extracted and stolen for witchcraft or organ donation; and a lack of trust in the healthcare system. To implement the procedure, it was suggested that extensive community sensitization should be done, space limitations in healthcare facilities overcome, healthcare workers should be trained and limited human resource should be addressed. Conclusion The implementation of MITS in Mbale, Eastern Uganda, is likely to be acceptable given sufficient training and sensitisation.